2011
DOI: 10.4028/www.scientific.net/kem.485.199
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Orientation-Controlled Epitaxial KNbO<sub>3</sub> Thin Film by Hydrothermal Method

Abstract: KNbO3 thin films were deposited at 240 oC on various kinds of single crystal substrates by hydrothermal method using aqueous solutions containing Nb2O5 and KOH. The deposition amount of the films was found not to be much dependent on the orientation and the surface roughness of the substrates, but on the electrical conductivity of the substrate. Epitaxial {100}, {110} and {111}-oriented KNbO3 films with ferroelectricity were grown on (100)c, (110)c, and (111)c -oriented SrRuO3//(100)SrTiO3 substrates, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…On the other hand, the homogeneous nucleation of the perovskite phase was not achieved at such a low temperature because the perovskite phase was not detected for the powders prepared at 120 °C. Taking account of the fact that KNbO 3 films were hardly obtained on Pt/(100)SrTiO 3 substrates even at 240 °C in our previous report, 38) inhomogeneous nucleation on the substrate covered by perovskite top layers is a key to obtaining perovskite KNbO 3 films even at a low deposition temperature applicable to the deposition on organic substrates.…”
Section: Low Temperature Depositionmentioning
confidence: 74%
See 1 more Smart Citation
“…On the other hand, the homogeneous nucleation of the perovskite phase was not achieved at such a low temperature because the perovskite phase was not detected for the powders prepared at 120 °C. Taking account of the fact that KNbO 3 films were hardly obtained on Pt/(100)SrTiO 3 substrates even at 240 °C in our previous report, 38) inhomogeneous nucleation on the substrate covered by perovskite top layers is a key to obtaining perovskite KNbO 3 films even at a low deposition temperature applicable to the deposition on organic substrates.…”
Section: Low Temperature Depositionmentioning
confidence: 74%
“…Moreover, conductive LaNiO 3 was selected as top layer of the substrate because it has the same perovskite structure as KNbO 3 and was ascertained to enhance the growth of KNbO 3 films even at a low deposition temperature. 36,38) LaNiO 3 was deposited at 100 °C by sputtering method.…”
Section: Methodsmentioning
confidence: 99%
“…[29][30][31] In order to enhance the ferroelectric and piezoelectric properties of hydrothermally deposited (K, Na)NbO 3 films, orientation control is one of the crucial factors as they strongly depend on the crystal orientation. [31][32][33][34][35] In addition, the orientation can also affect the film thickness of the resulting films, i.e., the deposition rate, as frequently observed for other perovskite-based ferroelectric films such as PZT films. 36) However few studies have reported the dependence of orientation for thin film used by the hydrothermal technique.…”
Section: Introductionmentioning
confidence: 90%
“…50 nm-thick LaNiO 3 -surface layers which are the conductive perovskite oxide were deposited at 350°C on Inconel foil by radio frequency magnetron sputtering method. This is because we have already demonstrated that the KNbO 3 film can be deposited on various substrates by using the conductive perovskite oxide surface layer [19][20][21] . After that, LaNiO 3 /Inconel foil was molded into a coil shape.…”
Section: Methodsmentioning
confidence: 99%